Developments in electrode design: structure, decoration and applications of electrodes for electrochemical technology1. Issue 11 (4th July 2018) - Walsh, Frank C; Arenas, Luis F; Ponce de León, Carlos
Abstract: The diversity of cell geometries and their use for electrochemical processing and energy conversion are concisely reviewed, updating earlier treatments, with an emphasis on an engineering approach to electrode design. Electrode size varies from several cm 2 in the laboratory to stacks containing hundreds of m 2 at the industrial plant scale, and currents can range from nA at laboratory to many 100 kA in industry. Electrode materials include metals, conductive ceramics and polymers, as well as polymer–metal or ceramic–metal composites. Area, electrocatalytic activity and functionality can be tailored by selecting an appropriate support structure‐coating combination. The core structure of porous supports can be a foam, mesh or particulate bed, whereas the surface can be enhanced using numerous techniques. Inspiration for electrode design can come from multiple sources, including biomimetics and technology transfer. Important aspects of electrodes include manufacture, electrochemical activity, active area, the possibilities of 3D and nanostructured surfaces, decoration and functionalization, in addition to reasonable cost and adequate lifetime. The diversity of electrodes is illustrated by examples from the authors' laboratory in the fields of inorganic and organic synthesis, environmental remediation of wastewaters, surface finishing of materials and energy storage/conversion. A forward look is made to potential future developments in electrochemical technology. © 2018 Society of Chemical Industry